The Role of Information and Communication Technology in the Development of Educational Curriculum - Haydar Abdul Jabbar; Juliyanti Wilia Putri; Elsya Nabila Fitri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The swift advancement of information and communication technology has significantly influenced numerous fields, particularly education. Incorporating ICT into the design of educational programs facilitates the development of learning experiences that are interactive, adaptable, and aligned with contemporary needs. This paper seeks to explore how ICT enhances the quality and efficacy of educational curricula. It highlights different technologies applicable in the educational process, including e-learning platforms, instructional software, and online applications that foster competency-based education. Furthermore, ICT promotes curriculum development that aligns closely with industry requirements and the needs of a global society. By effectively employing technology, curriculum design can become more attuned to the evolving landscape and challenges within education. Findings from this research demonstrate that ICT possesses considerable potential for driving curriculum innovation, broadening access to education, and enhancing both evaluation and learning processes. Nonetheless, the effective integration of ICT into curriculum design is contingent upon sufficient training for teachers and the adequacy of supportive educational infrastructure.